0216 The Sleep Environment: Associations between Household-level Factors and Actigraphy-based Sleep Duration and Disruption in the Jackson Heart Sleep Study (JHSS). (12th April 2019) - Johnson, Dayna A; Jackson, Chandra L; Guo, Na; Sofer, Tamar; Laden, Francine; Wilson, James; Redline, Susan
Abstract: Introduction: Suboptimal neighborhood environments are associated with poorer sleep health, but few studies have investigated the household-level environment in relation to sleep patterns. This investigation may be particularly relevant to African-Americans - a group disproportionately affected by insufficient sleep and adverse environments. We tested associations between household-level factors and activities in the bed with sleep duration and disruptions among African-Americans. Methods: A subset of JHSS participants (N=231) completed a sleep environment questionnaire and underwent 7-day wrist actigraphy. Self-reported sleep duration and actigraphy-based sleep duration, sleep efficiency and WASO were assessed. Perceived sleep environment was evaluated based on perceptions of safety, comfort, temperature, noise, and light disturbance. Participants reported activities in bed (e.g. watching television, listening to music, reading, eating). For each of the domains we created a score to estimate the combined effect of the included variables. Scores were constructed as weighted sums of the respective questionnaire items. We regressed each sleep outcome on all sleep environment components while adjusting for demographics. The weights were the positive estimated coefficients from the regression, or zero if the estimated coefficient was negative, normalized by dividing the coefficient by the sum, to obtain scores. Results: Participants were older in age (66.3 years, standard deviation=10.8), mostly female (69.7%), and college educated (44.6%). An increase in an adverse sleep environment score was associated with both a lower self-reported sleep duration (β=-109.2 minutes, 95% confidence interval: -204.8, -13.6) and sleep efficiency (β=-5.3%, -10.3, -0.3), but not actigraphy-based sleep duration nor WASO. Engaging in activities in bed was associated with a lower actigraphy-based sleep duration (β=-29.0 minutes, -54.1, -3.9), sleep efficiency (β=-5.2%, -8.0, -2.3), and a WASO of 23.6 minutes (9.1, 38.1), but not self-reported sleep duration. Conclusion: Perceptions of suboptimal environments were generally associated with shorter self-reported sleep duration whereas engaging in activities in bed was related to shorter objectively-measured sleep duration and greater sleep disruptions. Intervening on the sleep environment, including interventions around in-bed activities, may improve sleep among African-Americans. Support (If Any): NHLBI K01HL138211.